ChemInform Abstract: Formal γ‐Alkynylation of Ketones via Pd‐Catalyzed C—C Cleavage. Issue 37 (22nd August 2013) - Ziadi, Asraa; Correa, Arkaitz; Martin, Ruben
Abstract The presented method allows for the coupling of tert‐cyclobutanols, such as (I) and (VI) with bromoacetylenes, giving access to versatile alkynes (III) and (VIII), respectively.